The International Livestock Centre for Africa - Current research and applications - Nestel, Barry L. (Royal Agricultural Society of England, 1985)
Reviews the overall objective of ILCA, research areas concentrated and food production in Africa; presents the details of the field programmes grouped in four ecological zones; discusses briefly some aspects of the systems approach, appropriate technology and trypanotolerance.